Manajemen Preoperatif pada Protokol Enhanced Recovery After Surgery (Eras) - Sudadi; Anindita, Mohammad Pradhana; Kurniawaty, Juni (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Surgery and trauma stimulate metabolic, hormonal, haematological, immunological complex response and activate sympathetic nerve systems. Generally, stress response induced by surgery may causes dangerous impacts. Enhanced Recovery After Surgery (ERAS) is multimodal and multidisciplinary perioperative management approach designed for minimizing stress response, patient complication, length of hospital stay, and enhancing patient recovery. ERAS protocol or pathway includes preoperative, intraoperative, and postoperative management. ERAS preoperative management is started at preadmission phase. Preadmission management includes patient and family education and counseling, alcohol and smoking cessation, nutritional screening, patient’s health condition optimizing and coexist disease medication optimizing. Preoperative management includes carbohydrate treatment, fasting protocol, preoperative antibiotic prophylaxis, preoperative thromboembolic prophylaxis, and prophylaxis against nausea and vomit.